Comparison of regional brain atrophy and cognitive impairment between pure akinesia with gait freezing and Richardson's syndrome - Hong, Jin Yong; Yun, Hyuk Jin; Sunwoo, Mun Kyung; Ham, Jee Hyun; Lee, Jong-Min; Sohn, Young H.; Lee, Phil Hyu (Frontiers in Aging Neuroscience, 2015)
Pure akinesia with gait freezing (PAGF) is considered a clinical phenotype of progressive supranuclear palsy. The brain atrophy and cognitive deficits in PAGF are expected to be less prominent than in classical Richardson’s syndrome (RS), but this hypothesis has not been explored yet. We reviewed the medical records of 28 patients with probable RS, 19 with PAGF, and 29 healthy controls, and compared cortical thickness, subcortical grey matter volume, and neuropsychological performance among the three groups. Patients with PAGF had thinner cortices in frontal, inferior parietal, and temporal areas compared with controls; however, areas of cortical thinning in PAGF patients were less extensive than those in RS patients. In PAGF patients, hippocampal and thalamic volumes were also smaller than controls, whereas subcortical grey matter volumes in PAGF and RS patients were comparable. In a comparison of neuropsychological tests, PAGF patients had better cognitive performance in executive function, visual memory, and visuospatial function than RS patients had. These results demonstrate that cognitive impairment, cortical thinning, and subcortical grey matter atrophy in PAGF patients resemble to those in RS patients, though the severity of cortical thinning and cognitive dysfunction is milder. Our results suggest that PAGF and RS may share same pathology but that it appears to affect a smaller proportion of the cortex in PAGF.